PENERAPAN SISTEM PEWARISAN PATRILINEAL MASYARAKAT ADAT BATAK TOBA (PUTUSAN NOMOR 3494 K/PDT/2016) - Maria Raissa Sofia Rantan; Adiasih, Ning (Reformasi Hukum Trisakti, 2023)
The Patrilineal Kinship System, the inheritance system chosen by the Toba Batak people, places men in a greater position than women, particularly as heirs because men pass down the clan to their kids. The issue is how the judge evaluates the Toba Batak customary community's inheritance dispute in Decision Number 3494 K/Pdt/2016 and whether the resolution of the Toba Batak customary community's inheritance dispute in Decision Number 3494 K/Pdt/2016 is consistent with the patrilineal inheritance principle that has been applied to the Toba Batak community. The study utilizing deductive reasoning, qualitative analysis of secondary material and normative legal research approaches. The outcomes of the research, discussion and conclusion of this study are the judge's considerations in Decision Number 3494 K/Pdt/2016 considering letter evidence and witness statements, it is proven that if the disputed land was obtained by the biological mother of the Cassation Respondent who was previously purchased from the Nagari so that those who are entitled to inherit are the Cassation Respondent and the Toba Batak customary inheritance dispute settlement in Decision Number 3494 K/Pdt/2016 is not in accordance with the principle of patrilineal inheritance that has been in effect for the Toba Batak people.